CONCEPTUAL DESIGN AND ANALYSIS OF A TRICYCLE MOUNTED SOLAR-POWERED PHOTOVOLTAIC COLD ROOM SYSTEM (Nigerian Journal of Technology, 2024)
Energy crisis in developing countries is worrisome, and this has made the preservation and transportation of medical and perishable food items a common problem. Most conventional refrigeration systems operate with electricity; however, there are regions where it is difficult or not cost efficient to provide electric service. Therefore, this research seeks to solve the problems of inconsistent, irregular and complete non availability of power supply required to keep food products and drugs refrigerated over a long period of time by designing a tricycle mounted solar-powered cold room. The tricycle mounted solar-powered cold room designed consists of a refrigeration system having a compressor, a condenser, an expansion valve and an evaporator; a solar system having a photovoltaic (PV) module, charge regulator, storage battery and DC to AC inverter; and a tricycle for easy distribution and safe delivery of refrigerated items. A comprehensive analytical design was performed on each of the systems and the design results showed that the solar-powered cold room has refrigerating cooling load, PV array size, battery cap, and inverter power of 986 W, 275 W, 94 kWh, and 8000 W respectively. A structural analysis was also carried out on the tricycle chassis using the finite element method on Autodesk Inventor software. The results showed that the maximum von misses stress experienced by tricycle chassis was 56.96 MPa which is significantly lower than the yield strength of the chassis material used in the design, indicating a robust structural integrity and can therefore be used to carry the loads that it will be subjected to without deformation.